La controversia en torno al enfoque de género en el currículo nacional de educación básica en el Perú por parte de la campaña #ConMisHijosNoTeMetas - Alegría, Alicia (2020)
The essay discusses, by reviewing secondary sources, the controversies that have arisen around the implementation of the gender approach in the National Curriculum of Basic Education, concentrating on the discourse defended by social movements such as "Con mis hijos no te metas". We defend that, far from being a problem that belongs only to a “private” sphere that should not be interfered with, this has effects on health and public education. To approach the subject, we will resort to two theoretical paths. The first one, based on a Foucauldian analysis, has the objective of arguing that the sphere of sexuality reproduces “divisive practices” on the experience of sexuality, which maintain a logic of domination and stigmatization over sexual diversities. Therefore, it is not a problem that can be understood only as "intimate", but it is possible to recognize its social, political and economic implications. From the second path, we will observe the presence of the economic dimension, around which we will reflect, on the one hand, on the particular interests implicit in the discourse that link it with its ideological character, using the ideas of K. Marx. This will allow us, on the other hand, to emphasize the situation of greater vulnerability of the population of low socioeconomic levels. Finally, the importance of this problem being investigated not as a matter merely linked to the religious character of these groups, but also from its economic and political dimensions will be established.